Reflections on Translation Studies: Past and Present - Simon, Sherry (TTR, 2017)
This article is a reflection on translation studies and a suggestion for new directions in further research. The case study is that of the new labelling in the National Gallery of Canada which includes labelling in Indigenous languages.In June of 2017, the National Gallery opened newly renovated galleries with a special exhibition of Canadian and Indigenous Art. The translations which are part of this exhibition are important in redefining the identity of Canadian art.